Synthesis of a one-part geopolymer system for soil stabilizer using fly ash and volcanic ash - Tigue, April Anne S. (Animo Repository, 2018)
A novel approach one-part geopolymer was employed to investigate the feasibility of enhancing the strength of in-situ soil for possible structural fill application in the construction industry. Geopolymer precursors such as fly ash and volcanic ash were utilized in this study for soil stabilization. The traditional geopolymer synthesis uses soluble alkali activators unlike in the case of ordinary Portland cement where only water is added to start the hydration process. This kind of synthesis is an impediment to geopolymer soil stabilizer commercial viability. Hence, solid alkali activators such as sodium silicate (SS), sodium hydroxide (SH), and sodium aluminate (SA) were explored. The influence of amount of fly ash (15% and 25%), addition of volcanic ash (0% and 12.5%), and ratio of alkali activator SS:SH:SA (50:50:0, 33:33:33, 50:20:30) were investigated. Samples cured for 28 days were tested for unconfined compressive strength (UCS). To evaluate the durability, sample yielding highest UCS was subjected to sulfuric acid resistance test for 28 days. Analytical techniques such as X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscope/energy-dispersive X-ray spectroscopy (SEM/EDX) were performed to examine the elemental composition, mineralogical properties, and microstructure of the precursors and the geopolymer stabilized soil. © The Authors, published by EDP Sciences, 2018.